European Automobile CO2 Emissions: From Forecasts to Reality - Zachariadis, Theodoros (My University, 2007)
The voluntary agreement between the European Commission and the automotive industry to cut new car CO2 emissions by 25% between 1995 and 2009 is probably the most important EU initiative to curb carbon emissions as it addresses the road transport sector, whose growth may cancel out all other attempts to meet the EU’s Kyoto commitment. The paper evaluates progress in automobile fuel economy and CO2 emissions observed since 1995, examines the issue within the international context and attempts to assess whether further improvements are possible after 2010 in Europe. Based on data available up to mid-2005 it seems that, in the absence of strong technical progress and remarkable changes in consumer behavior until 2009, the industry’s commitment can only be met with some years’ delay. Moreover, it is most likely that technical progress will not persist in the future unless a policy mix of regulations and economic instruments is implemented.